1995
DOI: 10.1007/bf01719950
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion of thermophilicCampylobacter in the Pesaro-Urbino area (Italy) from 1985 to 1992

Abstract: The results of research on the spreading of campylobacter in the Pesaro-Urbino area carried out from 1985 to 1992 are presented. Materials of different origin were examined: 822 samples of human faeces, 533 animal rectal swabs, 192 samples of domestic sewage, 48 of river water, 96 of sea water and 632 of various types of food. Two hundred and nine strains of campylobacter were isolated (9%), most of which were Campylobacter jejuni (80%), with particular frequency in food products (chicken carcass 45.7%, ground… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
8
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 14 publications
2
8
0
Order By: Relevance
“…The isolation of C. jejuni (75%) and C. coli (16%) in this study has important implications for public health as C. jejuni is the species of Campylobacter most commonly involved in human Campylobacteriosis (Tauxe et al. 1987; Baffone et al. 1995; Nielsen et al.…”
Section: Discussionmentioning
confidence: 78%
“…The isolation of C. jejuni (75%) and C. coli (16%) in this study has important implications for public health as C. jejuni is the species of Campylobacter most commonly involved in human Campylobacteriosis (Tauxe et al. 1987; Baffone et al. 1995; Nielsen et al.…”
Section: Discussionmentioning
confidence: 78%
“…2007). However, there are few studies focused on river and seawater of the Mediterranean area (Alonso and Alonso 1993; Baffone et al. 1995; Moreno et al.…”
Section: Introductionmentioning
confidence: 99%
“…These studies have demonstrated campylobacter carriage rates peaking in late spring and summer in broiler chicken flocks ( 10 , 11 ) and dairy cattle ( 12 ) but more constant infection in lambs and beef cattle ( 12 , 13 ). Campylobacter has been successfully isolated and cultured from surface water in Finland ( 14 , 15 ), Italy ( 16 ), and NW England ( 17 ), and sporadic campylobacteriosis (illness not associated with an outbreak) has been linked with exposure to untreated water in Scandinavia ( 18 , 19 ). C. jejuni has also been isolated from a wide range of animal and environmental samples in a rural area in NW England, which suggests a potential environmental risk for exposure ( 20 ).…”
mentioning
confidence: 99%